The educational role of “self” in the literary and mystical thoughts of Mowlavi and Iqbal Lahori - Zaynab Rostaminasab (ادبیات تطبیقی, 2019)
Abstract In the philosophy of education, the educational role of self is considerably important. Therefore, this issue is comparatively investigated from the viewpoints of two wise scholars in two separate lands. The purpose of this article is to study the concept of “the educational role of self” and the way it is dealt with in ideology and thought systems of Jalal ad-Din Muhammad Rumi (Mowlavi) and Iqbal Lahori. By self, it is meant a person who is apt to know him/herself as well as the resources relevant to his or her growth and excellence. Human knows him/herself more than others do and plays a central role in the process of his/her own education and guidance; therefore, self-guidance is a major component of self-education. Thinking deeply about one’s nature and essence has been the objective of thinkers in education-based systems. In fact, “self” is responsible for all challenging issues of human’s social and personal life; in other words, every human being is responsible for solving his/her own problems and is being asked questions, accordingly. Education itself is an undeniable and effective fact in human life, thus, analyzing and investigating it has always been a significant necessity throughout the history of human life. Mowlavi and Iqbal believed that “self-education” prevents one from being submitted to his/her desires and also societies from adhering to profit and loss, prejudices and narrow-minded materialist and temporary views; therefore, it leads humans to prosperity. Humans gain excellence and prosperity during the process of education and “self” begins to play a significant role in this process from a certain point until the end of life, hence, it is of paramount importance to know this role. A review of the comparative researches on self or soul in the educational beliefs of Mowlavi and Iqbal indicated that no independent research has been conducted so far in this field. Therefore, it is significantly necessary to carry out this research. The question that arises is what are the similarities and differences between the approaches taken by Mowlavi and Iqbal regarding self-knowledge and the way it is taught?  The method of this research is qualitative and data relevant to these two scholars are described and analyzed. The findings indicate that with accordance to the social context in which they were educated, Mowlavi and Iqbal regard the strengths and weaknesses of the social and cultural systems of their time in terms of the education of “self”. Therefore, “self-education” is given priority in their educational system. The common aspect of recognizing and educating “self” for Mowlavi and Iqbal is the direct encounter of a person with divine nature, educating reason and awareness of natural phenomena. However, the difference between their views lies in the extent to which they use rationality and experience during “self-education”.  Mowlavi emphasizes intuitional knowledge and believes it is with the education of the seeker-mystic that a person becomes united with God and self-knowledge is resulted. Iqbal, nevertheless, applies the method of rational knowledge and its empirical results to expand the individual self to the social self and holds a collective view on education of “self”. In classical mysticism, about which Mowlavi wrote prose and poetry, self-knowledge is the main objective of self-education. “Trainers or those experienced in spiritual and mystical education, in the first step of education, must teach the trainee self-discovery, self-esteem and self-knowledge so as to provide him/her with a springboard for knowing God”. In his educational ideas, Mowlavi considers the movement towards God as the ultimate goal of education, which is presented in three sections: the macro, the middle and the micro. Macro principles of education: human responsibility for self-education, adjustment of the education process and curriculum appropriate to one’s capability and capacity, priority of intrinsic revolution over change in appearance, paying attention to psychological rather than physical education and multiplicity of cognitive pathways; middle principles: continuous self-assessment, trusting the trainer and giving priority to  purification of soul over knowledge; individual’s educational principles or educational methods: self-impose, presentation of insight about oneself and one’s situation and the method of love taught by parents to seekers. Allameh Iqbal Lahori considers the socio-cultural and political conditions of his time in addition to religious and mystical teachings when he defines the objective of the education of self or human soul. Based on his education in and deep thinking about modern teachings and sciences particularly philosophy, he consciously and critically investigated the foundations and fundamental layers of Islamic culture and civilization on the one hand and Western culture and civilization on the other and considered following a “Muslim self” as the secure way of passing dangerous paths leading to underdevelopment of the Islamic world. Like Mowlavi, Iqbal believes that determinism and separation of thoughts governing the Oriental people are the main causes of deviation in personal and social education leading to intellectual and scientific backwardness. For this reason, Iqbal believed that the East needed original thinkers to overcome the problems of their societies. Thus, he emphasized the excellence of the individual, which leads to the excellence of the society. In the educational systems of Mowlavi and Iqbal, expressing the principles of education of self or soul is the most important objective of the philosophy of education showing how human beings can have a self compatible and in harmony with the facts and events; the self that is also able to influence them. This is a principle. The second principle of self-knowledge and self-education in Mowlavi’s educational system is to learn science and knowledge. Mowlavi believes that science is derived from revelation given to prophets since the material nature of man cannot penetrate beyond the world of senses, so science belongs to whatever for which the revelation was made to prophets. For Mowlavi science is rational experience and discovery and even intuitive knowledge. Comparing the educational ideas of Mowlavi and Iqbal with an emphasis on self-education, it can be concluded that Mowlavi, having the conditions of his time into account, encourages the trainees to know themselves, discover their talents and utilize these talents to achieve the ultimate goal of education, which is to serve and worship God. Iqbal lives in an era when Western culture has partially penetrated Muslim countries and has brought about some changes. He does not consider education to be free of these influences and encourages trainees to know pure Islamic culture and get educated based on its teachings. In this regard, he pays considerable attention to the unity and solidarity of Islamic thinkers and considers their presence in a common theoretical and practical scene useful for education. Nonetheless, his ideas regarding the role of self in recognizing one’s duties and education are compatible with those of Mowlavi.